2014
DOI: 10.1111/jce.12405
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Delivery of Inappropriate Shocks Achieved by Remote Monitoring of ICD: A Substudy of the ECOST Trial

Abstract: RM was highly effective in the long-term prevention of inappropriate ICD shocks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 15 publications
0
53
0
2
Order By: Relevance
“…Even in the ECOST study, 23,46 in which the number of patients with appropriate shocks was more than twice the number of patients with inappropriate shocks, the number of patients who were administered appropriate shocks was similar in both the remote follow-up and control arms of the study (16.7% vs 17.5%; P = .84).…”
Section: Shock Reductionmentioning
confidence: 63%
See 1 more Smart Citation
“…Even in the ECOST study, 23,46 in which the number of patients with appropriate shocks was more than twice the number of patients with inappropriate shocks, the number of patients who were administered appropriate shocks was similar in both the remote follow-up and control arms of the study (16.7% vs 17.5%; P = .84).…”
Section: Shock Reductionmentioning
confidence: 63%
“…The ECOST study 23,46 evaluated ICD therapy events as a prespecified secondary end point and reported a significant reduction in inappropriate therapy for patients assigned to the RM arm. Over 27 months, the incidence of inappropriate shocks was 5.0% in the patients randomized to the RM group compared with 10.4% in the standard group (P = .04).…”
Section: Shock Reductionmentioning
confidence: 99%
“…Therefore, that study recommended programming a higher level of energy after ATP [172]. Finally, a substudy of the Effectiveness and Cost of ICD Follow-Up Schedule with Telecardiology (ECOST) study, which randomly assigned 433 patients to remote monitoring (n ¼221; active group) vs ambulatory follow-up (n¼ 212; control group), showed that remote monitoring was highly effective in the long-term prevention of inappropriate ICD shocks through early detection and prevention of AF with a rapid ventricular rate, nonsustained VT, or diverted VT episodes [173].…”
Section: Tachycardia Therapy Programmingmentioning
confidence: 99%
“…[21][22][23][24] Additional personalization of the alert programming, based on the clinical profile of each patient at the time of ICD implantation, evolving with the evolution of the disease, might further optimize RM. It is noteworthy that the medical response brought about changes in patient management in 92% of instances, representing a high return.…”
Section: Main Organizational Pointsmentioning
confidence: 99%
“…During a mean follow-up of 16±7 and median of 17 (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) months, 562 patients were enrolled. The baseline characteristics of the study population are shown in Table 1.…”
Section: Study Populationmentioning
confidence: 99%